2022
DOI: 10.1007/s12144-021-02472-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-control and procrastination among adolescent: The mediating role of multi screen addiction

Abstract: Self-control is always crucial in many areas of life. Therefore, self-control failure is the source of many of the difficulties people face in their lives and also at the center of several problems, especially among adolescents. In this regard, the purpose of the study was to examine the mediating role of multi-screen addiction (MSA) in the relationship between self-control and procrastination among adolescents by using structural equation modeling (SEM). A cross-sectional design and an online questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Additionally, COVID-19 has significantly affected people’s behavior and mental health (Liang et al, 2022; Şimşir et al, 2022). People have spent more time using screens, including computers, smartphones, and TVs, and engaging in activities like social media and video games during the global COVID-19 pandemic (Liang et al, 2022; Pang, 2021; Şimşir Gökalp et al, 2022). The study by Gao et al (2020) revealed that distress is positively associated with frequent social media exposure during the COVID-19 pandemic.…”
Section: Fomo and Social Media Addiction And As Serial Mediators Betw...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, COVID-19 has significantly affected people’s behavior and mental health (Liang et al, 2022; Şimşir et al, 2022). People have spent more time using screens, including computers, smartphones, and TVs, and engaging in activities like social media and video games during the global COVID-19 pandemic (Liang et al, 2022; Pang, 2021; Şimşir Gökalp et al, 2022). The study by Gao et al (2020) revealed that distress is positively associated with frequent social media exposure during the COVID-19 pandemic.…”
Section: Fomo and Social Media Addiction And As Serial Mediators Betw...mentioning
confidence: 99%
“…Self-control refers to the ability to resist or overcome immediate impulses to attain a long-term goal (Baumeister et al, 2007; Duckworth & Seligman, 2006). Many studies have explained the significance of self-control in behavioral addictions such as social media addiction (Ekşi et al, 2019), internet addiction (Özdemir et al, 2014), multi-screen addiction (Şimşir Gökalp et al, 2022), and mobile phone addiction (Peng et al, 2022). Additionally, poor self-control is associated with mental health problems (Kim et al, 2022; Nielsen et al, 2020; Özdemir et al, 2014).…”
Section: Fomo and Social Media Addiction And As Serial Mediators Betw...mentioning
confidence: 99%
“…The higher the social media addiction, the higher the tendency of learners to procrastinate their academic responsibilities in this new normal education. Learners who procrastinate lose their educational priorities, self-regulation, and time management (Melgaard et al, 2022, Lewis, 2022Gokalp et al, 2022). Prior studies discovered that social media addiction had an unfavorable effect on students' academic performance and overall well-being (Alaika et al,2020;Whelan et al, 2020;Navarro-Martinez & Pena-Acuna, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, parental attachment styles have also been found to be associated with adolescent procrastination, with maternal and paternal alienation in particular associated with significantly higher levels of procrastination [27]. Other research among adolescents has focused on uncontrolled Internet and smartphone use, which mediates relationships between procrastination and psychological functioning (e.g., sleep quality, stress; [28][29][30]). Beyond psychological traits and behaviours, other relevant research has focused on demographic characteristics that may shape procrastination.…”
Section: Introductionmentioning
confidence: 99%